COMPARATIVE ANALYSIS OF DIAGNOSTIC APPLICATIONS OF AUTOSCAN TOOLS ON VEHICLE SYSTEMS (Nigerian Journal of Technology, 2017)
The study was carried out in five institutions where motor vehicle mechanics trade is offered as automobile technology which includes, three centers where auto scan tools are used for vehicle repairs and two technical colleges in Enugu state that offer motor vehicle mechanics (MVM) trade. A total of 83 MVM trainers, teachers and instructors comprise the population for the study. Five research questions were raised and three null hypotheses tested at 0.05and 0.01 significance levels guided the study. A structured questionnaire with 3 items questions as checklist, 2 Auto scan tools were used for the study and test carried out on 5 vehicle systems at the 3 centers where Innova 1360B with snap shoot (AST1) was compared with Innova 1360B without snap shoot (AST2) were used for vehicle diagnosis. The instrument was validated by five experts and modifications were made in the instrument according to their recommendations. Analysis of variance (ANOVA) of a two- way classification experiment data with two observations per experimental unit was used for the evaluation. The results revealed that the efficiencies of AST1 and AST2  in performing the diagnosis because at 1% level of significance, the F-cal was 0.04 and F-tab was 8.65 but differ in performances on various vehicle systems because at 1% level of significance, the F-cal was 7.38 and F-tab was 7.01.http://dx.doi.org/10.4314/njt.v36i2.27